Odpowiedzi

2009-11-09T14:00:39+01:00
A)
(a-b)(a²+ab+b²)= a³ - b³

b)
(x²+x+1)(x²-x+1)=x⁴ - x³ + x² + x³ - x² + x + x² - x + 1 =
x⁴ + x² + 1

c)
(x-1)(x³ +x²+x+1)=x⁴ +x³+x²+x - x³ - x² - x - 1 = x⁴ - 1

d) (x+1)(x ³-x²+x-1)=(x + 1) (x²(x - 1) + (x - 1)) =
(x + 1) (x - 1) (x² + 1) = (x² - 1)(x² + 1) = x⁴ - 1
2009-11-09T14:08:37+01:00
A)a³ *a²b+b³
b)x do czwartej+x³+x²+x³-x²+x+x²-x+1
c)x do czwartej+x³+x²+x-x³-x²-x-1
d)x do czwartej-x³+x²-x+x³-x²+x-1
2009-11-09T15:23:10+01:00
A) (a-b)(a²+ab+b³)=a³+a²b+ab³-a²b-ab²-b⁴=a³+ab³-ab²-b⁴
b) (x²+x+1)(x²-x+1)=x⁴+x²+1
c) (x-1)(x³ +x²+x+1)=x⁴+x³+x²+x-x³-x²-x-1=x⁴-1
d) (x+1)(x³-x²+x-1)=x⁴-x³+x²-x+x³-x²+x-1=x⁴-1

;)